언어재활사의 임파워먼트 조직몰입, 이직의도 간 상관관계연구 - 이명순(Myung Soon Lee); 박현(Hyun Park) (언어치료연구, 2020)
목적: 언어재활사의 임파워먼트, 조직몰입에 관심을 갖고 언어재활사들을 대상으로 이들이 생각하는 임파워먼트 정도, 그리고 조직몰입, 이직의도 간의 관계를 살펴봄으로써 향후 언어재활사들의 인적 자원관리전략 수립을 위한 기초 자료를 제시하고자 하였다. 방법: 본 연구의 설문은 2020년 6월 1일부터 6월 30일까지 이루어졌으며 언어재활사들에게 설문을 실시하였으며 응답한 설문지 97개 중 응답하지 않은 문항이 있거나 불성실 응답으로 판단할 수 있는 자료 16부를 제외하고 81개를 분석 대상으로 하였다. 본 연구에서는 통계적 처리를 위하여 SPSS Ver. 18.0 통계 패키지를 이용하였으며 분석 방법은 다음과 같다. 각 항목에 대한 대상자들의 경향을 파악하기 위해 기술통계를 사용하였고, 각 영역에 대한 Speramann’s correlation과 근무 기간에 따른 임파워먼트 차이를 알아보기 위하여 Mann-Whitney 검정을 실시하였다. 결과: 첫째, 언어재활사들의 직무 의미성과 직무 역량, 자기결정성은 높은 편이었지만, 영향력은 그다지 높지 않았다. 둘째, 조직몰입은 대체로 높은 편이었지만, 이직의도는 낮았다. 셋째, 임파워먼트와 조직몰입의 양의 상관관계, 임파워먼트와 이직의도는 음의 상관관계가 나타났다. 넷째, 3년 이하와 4년 이상의 근무기간에 따른 임파워먼트는 집단 간 차이가 나타났다. 결론: 본 연구의 결과를 종합하여 보면, 언어재활사들의 임파워먼트와 조직몰입, 이직의도 간에는 관련성이 있다. 또한 조직 구성원인 언어재활사 개개인을 임파워시킴으로서 언어재활사들의 조직몰입을 향상시키고 이직의도를 낮출 수 있고 이러한 측면에서 임파워먼트의 역할은 중요하다는 것을 보여주고 있다. Purpose: The purpose of this study is to present basic data for establishing human resource management strategies of language therapists by examining the relationship between language therapists' empowerment, organizational commitment, and turnover intention and their thinking about empowerment. Method: A survey was conducted from June 1 to June 30, 2020, with a questionnaire given to speech therapists. Of the 97 questionnaires, 81 were analyzed as 16 questionnaires were left unanswered or were answered insincerely. SPSS Ver. 18.0 was used for statistical processing as follows. Descriptive statistics and the Spearamann's correlation were used to identify the tendency of the subjects for each item, and the Mann-Whitney U test was conducted to determine the difference in empowerment according to the working period. Result: Therapists' job meaning, job competence, and self-determination were high, but their influence was low. Organizational commitment was generally high, but turnover intention was low; there was a positive correlation between empowerment. In addition, there was a negative correlation between organizational commitment, empowerment, and turnover intention. Finally,there was a difference in empowerment between groups according to the period of work for less than 3 years and more than 4 years. Conclusion: TThe results of this study suggest that there is a relationship between empowerment, organizational commitment, and turnover intention of speech therapists. Also, by empowering individual speech therapists who are members of the organization, it is possible to improve the organizational commitment of speech therapists and lower the turnover intention. KCI Citation Count: 0